1976
DOI: 10.1148/120.2.399
|View full text |Cite
|
Sign up to set email alerts
|

Control of Dose Administered Once a Week and Three Times a Day According to Schedules Calculated by the CRE Formula, Using Skin Reaction as a Biological Parameter

Abstract: Patients with breast cancer were irradiated postoperatively to bilateral parasternal fields. The validity of the Cumulative Radiation Effect (CRE) formula for treatment once a week and three times a day was analyzed, and both schedules were compared with treatment once a day (five times a week). The biological radiation effect on normal tissue was studied by reflectance spectrophotometry of skin erythema and pigmentation. Early skin reactions were identical after irradiation daily and once a week, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The biological effects of fractioned irradiation can be estimated using the cumulative radiation effect formula [24]. This formula takes into account days of treatment, number of fractions and dose (rad) per fraction while CRE seems superior to rad in the characterization of irra diation treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The biological effects of fractioned irradiation can be estimated using the cumulative radiation effect formula [24]. This formula takes into account days of treatment, number of fractions and dose (rad) per fraction while CRE seems superior to rad in the characterization of irra diation treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The target dose ranged from 58 to 82 Gy, corresponding to CRE 18 to 20. 8 The difference in dose was because of variations in fractionation pattern and total treatment time. In no case were cervical nodes included in the radiation field.…”
Section: Radiotherapy Treatmentmentioning
confidence: 99%
“…In 1971, Kirk et al [2] presented a formula for calculating the biological effects on normal tissue, effects designated as the cumulative radiation effect (CRE). Their work was an effort to understand the results by Ellis and coworkers, to make an extended use of results concerning skin sensitivity and implement these in clinical practice [3,4]. In refining the formulas, our arsenal has been enriched with approaches that also take into account injured cells (Biological Effective Dose, BED) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The decision to incorporate radiotherapy in the treatment plan may be influenced by numerous variables, particularly the age of the child, extent of resection, risk of significant neurologic morbidity in the event of tumor progression, and presenting symptoms [2,3]. The debate regarding the use of radiotherapy stems from the concern of late effects in survivors, including neurocognitive deficits, hearing loss, vasculopathy, endocrinopathies and second malignancies [4][5][6][7][8]. As therapeutic techniques have improved, some studies have reported overall survival rates as high as 94-100% at 10 years [3,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%